Myeloid differentiation factor‐2 activates monocytes in patients with dilated cardiomyopathy. Issue 1 (29th June 2022) - Feldtmann, Rico; Kümmel, Andreas; Chamling, Bishwas; Strohbach, Anne; Lehnert, Kristin; Gross, Stefan; Loerzer, Lisa; Riad, Alexander; Lindner, Diana; Westermann, Dirk; Fielitz, Jens; Dörr, Marcus; et al.
Abstract: Plasma levels of myeloid differentiation factor‐2 (MD‐2), a co‐receptor of toll‐like‐receptor 4 (TLR4), independently predict mortality in patients with dilated cardiomyopathy (DCM). We tested whether monocyte activation by MD‐2 contributes to immune activation and inflammatory status in DCM patients. We found increased MD‐2 plasma levels in 25 patients with recent‐onset DCM (1250 ± 80.7 ng/ml) compared to 25 age‐ and gender‐matched healthy controls (793.4 ± 52.0 ng/ml; p < 0.001). Monocytes isolated from DCM patients showed a higher expression (141.7 ± 12.4%; p = 0.006 vs. controls) of the MD‐2 encoding gene, LY96 and an increased NF‐κB‐activation. Further, the TLR4‐activator lipopolysaccharide (LPS) caused a higher increase in interleukin (IL)‐6 in monocytes from DCM patients compared to controls (mean fluorescence intensity: 938.7 ± 151.0 vs. 466.9 ± 51.1; p = 0.005). MD‐2 increased IL‐6 secretion in a TLR4/NF‐κB‐dependent manner in monocyte‐like THP‐1‐cells as demonstrated by TLR4‐siRNA and NF‐κB‐inhibition. Since endothelial cells (ECs) are responsible for recruiting monocytes to the site of inflammation, ECs were treated with MD‐2 leading to an activation of Akt and increased secretion of monocyte‐chemoattractant‐protein‐1 (MCP‐1). Activation of ECs by MD‐2 was accompanied by an increased expression of the adhesion molecules CD54, CD106 and CD62E, resulting in an increased monocyte recruitment, which was attenuated by CD54 inhibition. In addition, in murine WT but not LY96 ‐KO bone marrow‐derived macrophages LPS increased the amount of CD54 and CD49d/CD29. MD‐2 facilitates a pro‐inflammatory status of monocytes and EC‐mediated monocyte recruitment via TLR4/NF‐κB. Elevated MD‐2 plasma levels are possibly involved in monocyte‐related inflammation‐promoting disease progression in DCM. Our results suggest that MD‐2 contributes to increasing monocytic inflammatory activity and triggers the recruitment of monocytes to ECs in DCM. Abstract : The myeloid differentiation factor‐2 (MD‐2), a co‐receptor of the toll‐like receptor‐4 (TLR4), is a biomarker and player in dilated cardiomyopathy (DCM) that contributes to immune activation: plasma levels of MD‐2 are significantly elevated in patients with recent‐onset DCM. MD‐2 stimulates pro‐inflammatory processes in macrophages and triggers monocyte recruitment to endothelial cells.